2008
DOI: 10.1007/s11606-008-0710-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Outpatient Telephone Coaching Add to Hospital Quality Improvement Following Hospitalization for Acute Coronary Syndrome?

Abstract: BACKGROUND: Telephone counseling in chronic disease self-management is increasing, but has not been tested in studies that control for quality of medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
(31 reference statements)
1
41
0
1
Order By: Relevance
“…The other studies have indicated that self-M a n u s c r i p t 20 management interventions did produce improved outcomes in physical activity (Hawkes et al, 2013;Furze et al, 2012;Holmes-Rovner et al, 2008), BMI (Zetta, et al, 2011;Muniz et al, 2010), reported statins intake (Muniz et al, 2010), vegetable intake (Hawkes et al, 2013) and fruit intake (Fernandes et al, 2009) when compared to usual care. Borderline statistical significance was demonstrated for BMI and alcohol consumption (Hawkes et al, 2013) as well as waist circumference (Muniz et al, 2010).…”
Section: Health Behavioural Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…The other studies have indicated that self-M a n u s c r i p t 20 management interventions did produce improved outcomes in physical activity (Hawkes et al, 2013;Furze et al, 2012;Holmes-Rovner et al, 2008), BMI (Zetta, et al, 2011;Muniz et al, 2010), reported statins intake (Muniz et al, 2010), vegetable intake (Hawkes et al, 2013) and fruit intake (Fernandes et al, 2009) when compared to usual care. Borderline statistical significance was demonstrated for BMI and alcohol consumption (Hawkes et al, 2013) as well as waist circumference (Muniz et al, 2010).…”
Section: Health Behavioural Outcomesmentioning
confidence: 99%
“…Of eight papers measuring health behavioural outcomes (Fernandes et al, 2009;Barlow et al, 2009;Hawkes et al, 2013;Muniz et al, 2010;Furze et al, 2012;Dalal et al, 2007;Zetta et al, 2011;Holmes-Rovner et al, 2008), two papers (Barlow et al, 2009;Dalal et al, 2007) did not report any difference between the two groups in terms of their health behavioural outcome measurement such as exercise capacity, smoking, BMI, BP, total cholesterol level, use of medication, coronary events and mortality. The other studies have indicated that self-M a n u s c r i p t 20 management interventions did produce improved outcomes in physical activity (Hawkes et al, 2013;Furze et al, 2012;Holmes-Rovner et al, 2008), BMI (Zetta, et al, 2011;Muniz et al, 2010), reported statins intake (Muniz et al, 2010), vegetable intake (Hawkes et al, 2013) and fruit intake (Fernandes et al, 2009) when compared to usual care.…”
Section: Health Behavioural Outcomesmentioning
confidence: 99%
See 3 more Smart Citations